In-vitro and in-silico determinations of HMG-CoA reductase inhibition potential of caffeic acid for therapeutics of hypercholesterolemia - Heera Ram, Chandra kala, Karishma Sen, Anita Sakarwal, Jaykaran Charan, Paras Sharma, Rajsekhar Roy, Surajit Ghosh (Journal of Applied Pharmaceutical Science, 2021)
The recent study was aimed to investigate in-vitro and in-silico determinations of the 3-hydroxy-3-methyl-glutarylcoenzyme A reductase [HMG-CoA reductase (HMGCR)] inhibition potential of the caffeic acid. The in-vitro assay shown the IC50 values of caffeic acid and pravastatin by 10.162 µM and 40.6 nM which performed up to 83.29% and 85.83% inhibition of HMGCR, respectively. Consequently, the kinetics of inhibition of HMGCR showed significant values of Km and Vmax of the caffeic acid (0.360198 ± 0.04251; 11.8% and 91.0863 ± 1.65; 1.811%) and pravastatin (10.325 ± 0.9372) [9.077%; 94.2661 ± 2.458 (2.607%)]. Consequently, the molecular docking revealed significant binding energy, bond length, and H-boding of caffeic acid with target enzyme of HMGCR. Accordingly, the interactions of protein–ligand complexes under cytosolic conditions were validated through root mean score fluctuation of molecular dynamics. Subsequently, the gastrointestinal absorption authenticated by the BOILED egg prediction is further validated by Absorption, Distribution, Metabolism, Excretion, And Toxicity (ADMET) assays and iLogP value. The drug likeness values of caffeic acid and pravastatin were found suitable as per the five rules of the Lipinski. Supportively, the toxicity profiles of the caffeic acid and pravastatin was made by the ProTox-II web server. Hence, it can be concluded that caffeic acid has the capabilities to inhibit HMGCR which provides the hypocholesterolemic potential.
Keywords: HMGCR, caffeic acid, pravastatin, molecular docking, ADMET